PLANNING FOR IMPROVING ROAD CLASS ON ROAD ACCESS TO RAHADI OESMAN AIRPORT KETAPANG-WEST KALIMANTAN - Saputra, Yogi Ayik; Winiasri, Linda; Purwayudhaningsari, Ranatika (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2024)
Rahadi Oesman Airport is located in Ketapang Regency, West Kalimantan. However, the airport terminal has different roads due to limited road access for vehicles, because residents use the terminal exit access to do things outside of aviation activities. The reference used is Ministerial Regulation No. 78 of 2014 and Standard Unit Prices for Goods Needed by the Ketapang Regency Government in 2024. The improvement plan for the road has an AC-WC layer thickness of 50 mm, a LFA of Class A 220 mm, a LFA of Class B 150 mm, and a stabilized subgrade layer of 200 mm, the calculation results are using the Road Pavement Design Manual method No. 03/M/BM/2024 with the required budget of IDR 525,560,000.00.